2011
DOI: 10.1080/11250003.2010.544333
|View full text |Cite
|
Sign up to set email alerts
|

Variability of the female genital system morphology and of sperm storage in terrestrial isopods (Isopoda, Oniscidea)

Abstract: In females of Isopoda Oniscidea, the genital system displays a remarkable variability of its morphological and functional organization as possible adaptation to different strategies of sperm storage. In all the oniscidean species, the sperm received from the male during mating are temporarily stored in the bursa copulatrix, a chitinous pouch of the oviduct. In 27 of the 32 species we studied, the sperm that remain in the bursa copulatrix after the fertilization of eggs of the first oviposition are transferred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The female genital system of the oniscidean isopods has been the object of numerous researches (Besse, ; De Luca et al, ; Legrand and Vandel, ; Longo and Trovato, ; Longo et al, ; Mazzei et al, ; Suzuki and Ziegler, ; Vandel, ; Warburg, ; Wägele ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The female genital system of the oniscidean isopods has been the object of numerous researches (Besse, ; De Luca et al, ; Legrand and Vandel, ; Longo and Trovato, ; Longo et al, ; Mazzei et al, ; Suzuki and Ziegler, ; Vandel, ; Warburg, ; Wägele ).…”
Section: Resultsmentioning
confidence: 99%
“…For the evaluation of the general characteristics of the female genital system some sexually mature and mated females were killed by decapitation and dissected in Ringer's saline solution modified for land isopods according to Legrand (Besse, ). The female genital system, after removal, was observed and photographed with the aid of a stereo‐microscope Wild M400, both fresh and after a brief fixation in 2.5% glutaraldehyde in 0.1 M phosphate buffer, pH 7.3; some specimens were in toto stained with Sudan black B (saturated solution in isopropyl alcohol) method that, as demonstrated in previous papers, clearly highlights the general organization of female genital system (Longo et al, ).…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…In all the three species examined the male genital apparatus is characterized by a basic morphological organization similar to that described for other species of terrestrial isopods (Vandel, 1925;Becker and Mann, 1938;Wägele, 1992); some degree of variability concerns only the location of the testis follicle on the cranial extremity of the seminal vesicle, that in T. alexandrae are inserted closely near to each other, and the genital tract that in H. hirsuta is longer so as to allow a greater accumulation of spermatozoa to be transferred with the mating inside the seminal receptacle female (Longo et al, 2011). The testis follicles are spindle-shaped but their size and their morphology varies notably according to the phase of spermatogenesis that in each of the three follicles is realized in a chronologically scalar mode.…”
Section: Discussionmentioning
confidence: 82%
“…Whilst some female isopods have both oöstegites and seminal receptacles (Longo et al . ), the latter are microscopic and would hardly preserve in fossils. Schram () suggested that the large opening on the eighth thoracic segment is a male genital cone, akin to that seen in the Order Tanaidacea (Peracarida); we agree.…”
Section: Discussionmentioning
confidence: 99%